Pengaruh dan Hubungan Brand Reputation, Brand Loyalty, Brand Attachment, dan Brand Equity Sebagai Variabilitas Penghubung (Studi Kasus Pada Konsumen Tiktok Shop Ms Glow di Indonesia) - Laili, Siti Nafisatul; Setiawan, Budi; Lukitaningsih, Ambar (Jambura Economic Education Journal, 2025)
The purpose of this study is to ascertain how brand reputation affects brand loyalty using case studies on Indonesian Tiktok Shop customers as mediating factors for brand attachment and brand equity. Quantitative research is the approach employed in this study. For this study, a questionnaire was used to gather data, and the SmartPLS version 3 program and computer help were used to do the analysis. Every sample utilized as a data source is an Indonesian who has purchased MS Glow items from Tiktok Shop. There were 206 people that responded. According to the findings, brand loyalty is negatively and negligibly impacted by brand reputation, while brand attachment is significantly impacted by brand reputation, brand loyalty is significantly impacted by brand equity, and brand equity is significantly impacted by brand loyalty.